Customer Loyalty Seen from the Aspects of Service Quality, Perceived Value and Customer Satisfaction and the Role of Switching Costs as Moderating Variables (Study on Goride Online Transportation in Manado City) - Junita Fadhillah Sigar; James DD Massie; Agus Supandi Soegoto (International Journal on Economics, Finance and Sustainable Development, 2022)
This study aims to analyze the effect of service quality, customer perceived value, customer satisfaction and the role of switching costs on customer loyalty to GoRide online transportation users. The population in this study were all GoRide Online Transportation users in Manado City. The sampling technique used purposive sampling technique as many as 100 samples. Data analysis used path analysis and moderated regression analysis (MRA) using SPSS 23. The results showed that service quality and perceived value simultaneously and partially had a significant effect on customer satisfaction. Perceived value has a significant effect on customer loyalty, while service quality has no significant effect on customer loyalty.